Magnetophonon Resonance in Quantum Wells with Parabolic Potential - Hoi, Bui Dinh; Lam, Vo Thanh; Phong, Tran Cong (Communications in Physics, 2012)
The linear dc magnetoconductivity in the$(x,y)$ plane of a parabolic quantum well, with a magnetic field$\vec B = B\vec e_z$ applied, is evaluated for electron - opticalphonon interaction. For nonpolar optical and polar optical phonons,the magneto-conductivity oscillates as a function of the magneticfield with resonances occurring when $Pω_c=ω_0$, where$ω_c$ and $ω_0$ are cyclotron frequency and optical phononfrequency, respectively, and where $P$ is an integer. The analyticresults are numerically evaluated to show explicitly the dependenceof magneto-conductivity on the magnetic field, the confinementfrequency in $z$ direction, and the temperature of the system